2D FE–DEM analysis of tractive performance of an elastic wheel for planetary rovers. (April 2016) - Nishiyama, Kenta; Nakashima, Hiroshi; Yoshida, Taiki; Ono, Tomomi; Shimizu, Hiroshi; Miyasaka, Juro; Ohdoi, Katsuaki
Highlights: 2D FE–DEM was applied to tractive performance analysis of an elastic wheel. Earlier code was updated by introducing a PID-controller model. Two-wheel traction analysis result curves matched those of experimental results. FE–DEM results for Mars show similar traction for wheels with different rigidity. Abstract: We have been developing a simulation program for use with soil–wheel interaction problems by coupling Finite Element Method (FEM) and Discrete Element Method (DEM) for which a wheel is modeled by FEM and soil is expressed by DEM. Previous two-dimensional FE–DEM was updated to analyze the tractive performance of a flexible elastic wheel by introducing a new algorithm learned from the PID-controller model. In an elastic wheel model, four structural parts were defined using FEM: the wheel rim, intermediate part, surface layer, and wheel lugs. The wheel rigidity was controlled by varying the Young's Modulus of the intermediate part. The tractive performance of two elastic wheels with lugs for planetary rovers of the European Space Agency was analyzed. Numerical results were compared with experimentally obtained results collected at DLR Bremen, Germany. The FE–DEM result was confirmed to depict similar behaviors of tractive performance such as gross tractive effort, net traction, running resistance, and wheel sinkage, as in the results of experiments. Moreover, the tractive performance of elastic wheels on Mars was predicted using FE–DEM. Results clarified that no significant difference of net traction exists between the two wheels.